Nueva localidad para el trepatroncos gigante (Xiphocolaptes Promeropirhynchus) en el Estado de Guerrero, México. - Argote Cortés, Aquiles (Instituto de Ecología, A.C., 2009)
In February of 2006 an individual of the Strong-billed Woodcreeper was sighted near the locality ofJuvinani, municipality of Metlatonoc, in the Mexican state of Guerrero. This is the first sighting reported for thisspecies in the region and increases its distribution in 135 km within the state of Guerrero.